Harmonics of the real-space velocity in cyclotron resonance experiments on organic metals - Blundell, S; Ardavan, A; Singleton, J (1997)
Electrons in cyclotron orbits around closed pockets in the Fermi surfaces of organic metals possess an oscillating real-space velocity. Higher harmonics of this real-space velocity lead to predicted cyclotron resonances additional to those normally expected. We calculate these resonances semiclassically using the Boltzmann transport equation. These higher harmonics are expected to occur remarkably often, and we show that they are found even in a very simple tight-binding model. A similar effect occurs in quasi-one-dimensional Fermi surfaces which are highly corrugated and in this case the oscillating part of the real-space velocity as it traverses the Fermi surface can couple directly to the microwave frequency.